Molecular identification and prevalence of ehrlichia canis and anaplasma platys in dogs in selected areas of Malaysia - Nazari, Mojgan (2011)
Ehrlichia species are the etiological agents of emerging and life-threatening tick-borne diseases of both humans and animals. They have been implicated in serious and fatal infections in companion animals and livestock and the potential to cause severe life-threatening diseases emphasizes the need for early diagnosis of ehrlichiosis. Limited studies have been conducted to investigate tick-borne diseases in Malaysia, and only two studies have been published on Ehrlichia canis thus far, the first one relied solely on light microscopic detection techniques and the other on immunofluorescence antibody test (IFA) test for diagnosis. The objective of this study was to carry out a molecular study of the 16S rRNA gene of Ehrlichia canis (E. canis) and Anaplasma platys (A. platys) infections in dogs in Malaysia using the polymerase chain reaction (PCR) technique which is known to be the most sensitive and specific method for the diagnosis of canine ehrlichiosis worldwide. For this purpose, canine blood samples were collected from pet dogs (n=323) presented to veterinary clinics and stray dogs (n=177) from February 2009 to February 2010. After DNA extraction, standard PCR was performed with a genus-specific set of primers EHR16SD, and EHR16SR followed by E. canis spices-specific PCR (CANIS/ GA1UR), and A. platys species-specific PCR (PlatysF/ PlatysR). Analysis of PCR products revealed that 2.0% (n=10) of dogs were positive for E. canis, (1.2% among the clinic group, and 3.4% among the stray dogs), and 4.6% (n=23) were positive for A. platys (1.2% and 10.73% among clinic group and stray dogs respectively). The sex, age, and breed of the clinical cases were noted and hematological and serum biochemical results were also obtained for the clinic group. Statistical analysis showed no consistent significant differences between E.canis or A.platys infection status, sex, age, breed, and clinical or hematological abnormalities. In order to achieve a larger size for sequence analysis, all positive samples were amplified with another set of primers (FD1/RP2). Sequence analysis of positive samples for both E.canis and A.platys showed 100% identity to a number of registered strains in NCBI GenBank. In conclusion the present study revealed for the first time the presence of genetically confirmed E. canis and A. platys pathogens with an overall prevalence rate of 2.0% and 4.6%, respectively in naturally infected dogs in Malaysia.